Pengembangan UMKM Jamu Dusun Sumberdadi,Jombang Melalui Re-Branding Identitas Logo Njampi - Mario Dhava Ferdyansyah; Panji Bagus Ramadhan; Dynda Tri Widyastuti; Nur Lathifa Meida; Moch. Rizky Ramadhan; Kusuma Wardhani M; Eka Restu Justitian (KARYA UNGGUL - Jurnal Pengabdian Kepada Masyarakat, 2022)
This article discusses the redesign of the branding design from Njampi. The function of re-branding is for the formation of product identity and characteristics. Due to the increasing competition between competitors. Njampi is a brand name for UMKM products in Sumberdadi Hamlet, Jombang which is engaged in the beverage sector. Njampi produces a variety of healthy herbal drinks such as tiger collar, betel nut, turmeric tamarind, kencur rice. Njampi already had a logo before but it didn't contain the character that matched the product, so with that, the logo was re-branded according to the character that represented the beverage product. Based on the analysis of the literature study, the logo uses the concept of color, typography and composition that gives a professional impression according to the characteristics of the product.